1985
DOI: 10.1002/jsfa.2740360602
|View full text |Cite
|
Sign up to set email alerts
|

Cassava foliage: Chemical composition, cyanide content and effect of drying on cyanide elimination

Abstract: The chemical composition and cyanide concentration in the foliage of four cassava cultivars (M Col 113, M Col 22, M Col 1684, CM 342-170) were evaluated at four plant ages (6, 8, 10 and 12 months). The effect on cyanide elimination of sun-drying on a concrete floor and of oven-drying at 60°C was also studied, including some observations on the tannin content of dried foliage. The proximal composition, calcium and phosphorus contents, as well as the amino acid composition of dried cassava foliage compared favo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
2

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 13 publications
4
25
0
2
Order By: Relevance
“…Table 2 shows the polyphenol contents, trypsin inhibitor, saponin and the hemagglutinative activity of CLM from these five cultivars at TAP. In general, it is observed that the polyphenol contents increased with the maturity of the plant, and this tendency was already described 21 .…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…Table 2 shows the polyphenol contents, trypsin inhibitor, saponin and the hemagglutinative activity of CLM from these five cultivars at TAP. In general, it is observed that the polyphenol contents increased with the maturity of the plant, and this tendency was already described 21 .…”
Section: Resultsmentioning
confidence: 57%
“…This wide variation is probably due to the genetic differences among the cultivars, the plant ages, the leaf drying temperatures, the leaf maturity, the soil fertility and the pluviometric precipitation index. The influence of the lack of rainfall events on the reduction of cyanide contents is reported 11,21 . For this reason, the data of the pluviometric precipitation were collected from the planting period (October/2000) until the last collection of the leaves (March/2002), and are shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing the contents of magnesium and calcium in CLM (g/100 g DM) with data reported in the available literature, that is, 0.26 to 0.97 for magnesium [9,16,20,23] and 0.04 to 1.63 for calcium [1,6,15,16,23,9], lower magnesium and similar calcium contents were observed, except for the Ouro do Vale cv. ones with higher levels for calcium at all TAP.…”
Section: -Results and Discussionmentioning
confidence: 58%
“…Cassava leaves were used in the study came from various varieties aged 8-10 months was taken from the experiment station of State Polytechnic of Lampung. Cassava leaves treated with a combination of chopping 2-3 cm, wilting 24 hours at room temperature, and drying it under the sun for 2 days (Gomez and Valdivieso, 1985). Milling cassava leaves and other feed ingredients in the form of grain using semi-fixed a hammer mill machine with a screen 2, 3, and 5 mm, while the feed material in the form of mash not grinded.…”
Section: Methodsmentioning
confidence: 99%